Success management as a PM knowledge area – work-in-progress - Varajão, João (2016)
It is a fact that an organization's success is closely linked with its projects’ success. Although there are many studies in literature that focus on different aspects of project success like, for instance, the success factors or the criteria for success assessment, there are only few studies that mention the processes required for success evaluation. Guides and standards, such as the PMBOK 5 or ISO 21500:2012, are not exceptions to this reality. Given the high importance and complexity of the evaluation of the projects’ success, in this work-in-progress the Success Management is proposed as a new knowledge area of project management, as well as a set of processes to be carried out in its scope